The Value of Protein, B-carotene and Sensory in Baby Biscuits made from Yellow Sweet Potatoes, Green Bean Sprouts and Fermented Millet Flour - Pratiwi, IDP Kartika; Arihantana, NM Indri Hapsari (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
Innovation baby biscuits from composite flour using local raw material such as yellow sweet potatoes, green bean and millet is important to diversification. This research aims to determine the protein content, ?-carotene and sensory properties of Baby Biscuits from 9 types composite flour formulas. The experimental design was a complete randomized design with a 9 composite flour formulas and repeated 2 times, the proportion of yellow sweet potatoes flour : green bean sprouts flour : fermented millet flour namely 60:25:15; 55:30:15; 50:35:15; 55:25:20; 50:30:20; 45:35:20; 50:25:25; 45:30:25; 40:35:25. The results of the analysis stated that the comparison of the composition of composite flour has a significant effect on the value of protein, ?-karoten, sensory test of taste and crispness of baby biscuits. The best formulation was obtained in baby biscuits made with the propotion of yellow sweet potatoes flour : green bean sprouts flour : fermented millet flour of 50:35:15. Those baby biscuits contained 8.51% protein, 398.18 g/100g ?-carotene, taste is like (5.93) and crispness level is crispy (4.20).